A comprehensive study to determine effect of coronavirus disease on pulmonary function of the affected patients - Amita R Ranade,; Anita J Jadhav,; Smita Y Wagh, (Asian Journal of Medical Sciences, 2023)
Background: As the global coronavirus disease-2019 (COVID-19) pandemic continues to unfold, understanding the implications of the disease on post-recovery lung function becomes crucial. This study aimed to investigate the early convalescent phase characteristics of lung function in patients recovering from COVID-19, shedding light on the extent and nature of lung impairments following acute infection. Aims and Objectives: This study aimed to investigate the early convalescent phase characteristics of lung function in patients recovering from COVID-19, shedding light on the extent and nature of lung impairments following acute infection. Materials and Methods: A cross-sectional analysis was conducted on 57 patients who had been diagnosed with COVID-19 and subsequently discharged from the hospital. Comprehensive lung function tests, chest computed tomography scans, and the 6-min walk test were performed approximately 30 days after discharge to assess pulmonary parameters, imaging abnormalities, and exercise tolerance. Results: The study revealed that more than half of the patients exhibited impairments in diffusing capacity (DLCO), respiratory muscle strength, and lung imaging abnormalities during the early convalescent phase. Notably, severe cases demonstrated a significantly higher incidence of DLCO impairment, accompanied by notable reductions in total lung capacity and 6-min walking distances compared to non-severe cases. Interestingly, the severity of illness or residual imaging changes did not consistently correlate with the observed lung function impairments. This observation challenges previous assumptions and underscores the complexity of the relationship between disease severity and post-recovery lung function. Conclusion: In the context of COVID-19 recovery, this study highlights the presence of early convalescent phase impairments in lung function, suggesting that the impact on respiratory health extends beyond the acute phase of infection.